Did they prepare you for this? ; a study of the adequacy of the undergraduate medical training for hospital practice in Malaysia - Omar, Azura; Abd. Manaf, Noor Hazilah; Adewale, Abideen Adeyami; Ismail, Izhairi; Abdul Hamid, Zabeda (2011)
Concerns over the quality of medical education has received renewed attention in Malaysia following a front page headline entitled “Quality first, not quantity” of a mainstream popular newspapers The Star on January 9, 2011. Indeed, this worry about the training given to physicians at medical school warrant serious examination. The consequences of having significant numbers of poor quality personnel in other areas of human activity may not be significant, but in healthcare, it can be a matter of life and death for all the population. Notwithstanding the importance of the issue at hand, very few studies (none in Malaysia) to date have examined the role of undergraduate training in preparing doctors capable of delivering the required standard of care (Hill et at, 1998). This study attempted to fill this void by examining the perception of housemen on the adequacy of their undergraduate medical training for hospital practices in Malaysia. Adapting the work done in Australia (Hill et al, 1998) and the UK (Paolo and Bonaminio, 2003), the study looked at eight subscales of preparedness for hospital practices which were interpersonal skills, basic skills, holistic skills, coping skills, ethics, patient management skills, scientific knowledge and clinical skills. Data was collected from 1213 housemen from 32 training hospitals in Malaysia. Overall, the data suggested that the housemen do generally believed that their medical training was adequate. However, further scrutiny of the data points to possible key differences based on medical training curriculum, indicating that the schools in which the housemen attended may have an influence on their “transition” from undergraduate to practicing professionals.